Cytotoxicity of allitinib, an irreversible anti-EGFR agent, in a large panel of human cancer-derived cell lines: KRAS mutation status as a predictive biomarker - Oliveira, Renato José Silva (2016)
The epidermal growth factor receptor (EGFR) is a member of the HER family of growth factors that activates several intracellular signaling pathways promoting proliferation and survival. EGFR over-expression is frequently associated with gene mutation or amplification, thereby constituting a major target for molecular therapies. Recently, a new generation of EGFR inhibitors has been developed with pan-HER properties and irreversible actions. AllitinibA (R) (AST1306) is an orally active, highly selective irreversible inhibitor of the HER family of receptor tyrosine kinases with promising efficacies. In the present study we aimed to investigate the cytotoxicity of allitinib in a large panel of human cancer-derived cell lines and to correlate its efficacy to the mutational status of the EGFR, KRAS, BRAF, PI3KCA and PTEN genes. In addition, we aimed to evaluate the functional role of KRAS mutations in the response to this new inhibitor. In total 76 different cancer-derived cell lines, representing 11 distinct histological types, were analyzed and classified into three groups: highly sensitive (HS), moderately sensitive (MS) and resistant (R). We found that 28 (36.8 %) cancer-derived cell lines exhibited a HS phenotype, 19 (25.0 %) a MS phenotype and 29 (38.1 %) a R phenotype. Allitinib showed a stronger cytotoxicity in head and neck, esophageal, melanoma and lung cancer-derived cell lines. We found that KRAS mutations were significantly associated with the R phenotype. To substantiate these results, an allitinib-sensitive lung cancer-derived cell line (H292) was transfected with plasmids carrying the two most common activating KRAS mutations (p.G12D and p.G12S). We found that both mutations reverted the allitinib-sensitive phenotype in these cells. The current study represents the largest in vitro assessment of allitinib cytotoxicity performed to date. Through this study, we identified cancer types that could potentially benefit from this drug. Additionally, our findings suggest that prevalent KRAS mutations constitute potential predictive biomarkers for allitinib response.